Bakhtin e Paulo Freire: a relação do eu e do outro e as relações dialógicas para a prática da liberdade - Silva, Danitza Dianderas da (2012)
This doctoral thesis is part of the line of research Teaching and Learning Processes . The aim of this study was to discuss dialogical relations between the self and the other on the perspectives of the authors Bakhtin and Paulo Freire, in order to promote the practice of freedom within the school. We conducted this discussion including the concepts of ethics, aesthetics, ideology, consciousness and language. Both authors emphasize the historical, subjective and ideological character in the formation of the self and the other and the dialogical relations emphasizing the horizon of possibilities that constitutes them. We stress that the action of teaching can encourage the practice of listening in their training, as well as in the student s; it also brings forward the importance of the teacher in the learning how to read the world and the word, favoring the quest for transformation and freedom. We can notice that in the schooling process the reading and writing practice may allow us teachers and students, to become critics and show responsiveness, thus, to search for liberty and transformation. It was possible to be noticed, along our study, that the self is, in Freirean and Bakhtinian perspective, necessarily formed by the interaction with the other, an important relation in the formation of consciousness, ideology, and also of responsibility (ethics combined with aesthetics), that conceive different dialogical relations, without which they may not be, without a self, without an other. We were able to observe the different dialogical relations for Bakhtin and Paulo Freire which allow the formation of a self commited to an other, to the world, in search for freedom. We conducted the discussion on education, regarding specifically the role of the progressive educator in teaching, and the importance of literacy, the reading the world, the reading and writing words. Hopefully this study will contribute to understanding the relations between the self and the other, between the teacher and the student, within school and in life.